2019
DOI: 10.3390/ijms20030724
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Surfaces Coated with Covalently Immobilized Collagen Type I: An X-Ray Photoelectron Spectroscopy, Atomic Force Microscopy, Micro-CT and Histomorphometrical Study in Rabbits

Abstract: Background: The process of osseointegration of dental implants is characterized by healing phenomena at the level of the interface between the surface and the bone. Implant surface modification has been introduced in order to increase the level of osseointegration. The purpose of this study is to evaluate the influence of biofunctional coatings for dental implants and the bone healing response in a rabbit model. The implant surface coated with collagen type I was analyzed through X-ray Photoelectron Spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 33 publications
1
38
2
Order By: Relevance
“…Yu et al [131] applied picosecond laser ablation to modify Ti substrate and demonstrated that the resultant surface of Ti with micro-groves promoted cell adhesion. The subtractive modifications of biomaterial surface may also be applied to prepare the surface before the coating process (Figure 4) [132][133][134][135][136][137][138][139]. By increasing the roughness of the surface, better adhesive bond between the coating and the surface of modified material may be achieved [140].…”
Section: Subtractive Modifications Of Biomaterials Surfacementioning
confidence: 99%
“…Yu et al [131] applied picosecond laser ablation to modify Ti substrate and demonstrated that the resultant surface of Ti with micro-groves promoted cell adhesion. The subtractive modifications of biomaterial surface may also be applied to prepare the surface before the coating process (Figure 4) [132][133][134][135][136][137][138][139]. By increasing the roughness of the surface, better adhesive bond between the coating and the surface of modified material may be achieved [140].…”
Section: Subtractive Modifications Of Biomaterials Surfacementioning
confidence: 99%
“…Oral implant rehabilitation is a highly predictable procedure characterized by 10-year success rates of over 97% [1][2][3]. Bone healing around the implant surface is influenced by different factors such as heat generation during implant site preparation [4,5], insertion torque, micro and macro implant surface characteristics, and quality of bone [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The scan rate was 0.1 Hz, and each disk was analyzed in four different areas of 10 µm × 10 µm, as previously described [29]. The Nanoscope Analysis software (1.5, Bruker, Milan, Itay) was used for measuring the average roughness, Ra, and the root-mean-square roughness of profile, Rq, with the respective standard deviations (SD).…”
Section: Atomic Force Microscopymentioning
confidence: 99%